Business Establishment among BBS Graduation: A Case Study in Pokhara Valley - Pudasaini, Sachin; Mahato, Nikita; Adhikari, Gopi Raj (Janaprakash Journal of Multidisciplinary Research, 2025)
Owning a business, whether large or small, has become a trend especially among youths including those in Nepal. Student life is considered the most crucial stage in an individual’s life, as it is the period when individuals choose the path they wish to pursue. This study aims to examine the extent to which Bachelor of Business Studies (BBS) students in Pokhara Valley are fascinated in establishing their own business. This study focuses on describing students’ aspirations toward business ownership and provides suggestions for addressing unemployment, one among major problems in Nepal. A qualitative primary survey was performed s to collect primary data from 110 bachelor-level students through self-administered questionnaires. The focus of research is in Jayaprakash Multiple Campus and Triveni International College, Pokhara. Total 20 different questions, including demographic variables, have been developed for data collection. And, reviewed, organized and then presented in a tabular and diagrammatic form. The findings revealed that the majority of the participants expressed interest in owning a business while only a small percentage of participants did not agree and preferred stable salaried employment. Many respondents believe in their entrepreneurial skills and knowledge and have confidence in themselves to operate a business. However, lack of investment, limited family support, and insufficient government assistance are identified as major challenges ahead.